Implantación de la contabilidad agropecuaria y análisis financiero de la hacienda ganadera Salapa San Isidro, de la ciudad de Loja periodo mayo - 2016 - Vinces Córdova, María del Pilar (2017)
The development of this thesis work was developed as a prerequisite to choose the degree of Engineering in Accounting and Auditing, Auditor Public Accountant, adjusting to the regulation of the Academic Regime in current validity When implementing the Agricultural Accounting and Financial Analysis in the Treasury, the objectives set at the beginning of the investigation were fulfilled, starting with the theoretical basis with subjects related to agricultural accounting, The determination of cost elements and the preparation of the plan and accounting manual, which was performed according to the needs of the company, served to detail the assets, liabilities, assets, revenues, costs and expenses. Same that they maintain a logical and orderly form with its respective codification allowing to carry an adequate record of the daily operations, Being the starting point for the elaboration of the Accounting Process from the Initial Inventory to the obtaining of the Financial Statements, followed by the application of the financial analysis, to fulfill the purpose of the correct decision making, in this way to help solve the weaknesses detected Of the hacienda. These results allow to have a clearer vision of the elaboration and determination of the costs and expenses in each one of the productions that realizes, in addition to the elaboration of the financial statements a loss could be evidenced, due to the maladministration and ignorance of the Laws and accounting standards.